A newly recognized syndrome of marfanoid habitus; Long face; Hypotelorism; Long, thin nose; Long, thin hands and feet; and a specific pattern of language and learning disabilities - Giacheti, Célia Maria [UNESP]; Zanchetta, Sthella; Maranhe, Elizandra; Cassab, Tatiana V.; Abran-Tides, Dagma V.; Souza, Deise H.; DeVitto, Luciana P. M.; Richieri-Costa, Antonio (Wiley-Blackwell, 2007)
Here, we report on a newly recognized syndrome in a Brazilian family with three affected women, who had a Marfanoid habitus; long face; hypotelorism; long, thin nose; long, thin hands and feet; and language and learning disabilities. The disorder is compatible with autosomal dominant inheritance. (C) 2007 Wiley-Liss, Inc.
Keywords: tall stature; minor facial anomalies; specific language and learning problems; autosomal dominant inheritance; new syndrome; 22q21 region